Solution focused therapy for the helping professions - Winbolt, Barry, 1946- (Jessica Kingsley Publishers, 2011)
This accessible guide to Solution Focused Brief Therapy (SFBT), an effective therapeutic approach which focuses on strengths and achievements, provides a practical introduction to what SFBT is and how to use it with clients.